2012
DOI: 10.1074/jbc.m112.422733
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerase ϵ Is Able to Efficiently Extend from Multiple Consecutive Ribonucleotides

Abstract: Background: Ribonucleotides in DNA are associated with genome instability.Results: Human DNA polymerase ϵ catalyzes efficient incorporation of ribonucleotides and extension from primers terminating in multiple consecutive ribonucleotides.Conclusion: Human DNA polymerase ϵ is able to extend ribonucleotide-terminal primers through a reduction in its proofreading activity.Significance: Leading strand replication may have a unique relationship to ribonucleotides, RNA, and genome stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 49 publications
1
57
1
Order By: Relevance
“…The small differences in exonuclease rates are in agreement with in vitro fidelity measurements on gapped substrates that showed that the two forms of Pol ⑀ have comparable levels of fidelity (45). The exonucleolytic rate obtained for yeast Pol2 core and Pol ⑀ (ϳ11 s Ϫ1 at 25°C) on a correctly base-paired primer-template are more than 10-fold higher than the reported value for the human Pol2 core (0.86 s Ϫ1 at 37°C) (46). The difference between the studies might in part be due to differences in the design of the experiments as well as to differences in sequence context.…”
Section: Discussionsupporting
confidence: 64%
“…The small differences in exonuclease rates are in agreement with in vitro fidelity measurements on gapped substrates that showed that the two forms of Pol ⑀ have comparable levels of fidelity (45). The exonucleolytic rate obtained for yeast Pol2 core and Pol ⑀ (ϳ11 s Ϫ1 at 25°C) on a correctly base-paired primer-template are more than 10-fold higher than the reported value for the human Pol2 core (0.86 s Ϫ1 at 37°C) (46). The difference between the studies might in part be due to differences in the design of the experiments as well as to differences in sequence context.…”
Section: Discussionsupporting
confidence: 64%
“…The increased number of errors in the dpb2-100 mutant could be caused by an increased incorporation of ribonucleotides, since Pol has previously been shown to incorporate ribonucleotides efficiently [65][66][67][68]. To check this possibility, we investigated whether the deletion of rnh201 (a component of RER-ribonucleotide excision repair) disturbs the removal of ribonucleotides from DNA, increasing the rate of mutations in the dpb2-100 strain.…”
Section: Errors In Dpb2-100 Strain Are Not Due To Increased Incorporamentioning
confidence: 98%
“…We used site-directed mutagenesis to introduce several CRC and endometrial cancer mutations into our previously described POLE expression construct (Korona et al 2011;Goksenin et al 2012), containing all six conserved motifs necessary for 39-59 exonuclease and DNA synthesis activities (Supplemental Fig. S3A).…”
Section: Mutation Of Pole-exo Impairs 39-59 Exonuclease Activitymentioning
confidence: 99%
“…Expression and purification of recombinant cancer-associated human POLE constructs An expression vector encoding amino acid residues 1-1189 of the exonuclease-proficient catalytic subunit of human POLE (POLE-N140) was used as described (Korona et al 2011;Goksenin et al 2012). Site-directed mutagenesis was used to introduce the POLEexo* mutations encoding: P286H, F367S, and S459F substitutions.…”
Section: Mutation Context Clustering and Enrichmentmentioning
confidence: 99%